Comorbidity, disability, and healthcare expenditure of ankylosing spondylitis in Korea: A population-based study. - Jeong Seok Lee; Baek-Lok Oh; Hee Young Lee; Yeong Wook Song; Eun Young Lee (PLoS ONE, 2018)
Ankylosing spondylitis (AS) is an inflammatory rheumatic disease typically diagnosed in young age and follows a chronic progressive course. Its impact on the patient is life-long and the burden that AS exerts on society is increasing cumulatively every year. We aimed to quantify the burden of AS and to identify the factors associated with comorbidity, disability, and healthcare expenditure in Korean AS patients.We conducted a nationwide, population-based study using health insurance data (2003-2013). The analysis included individuals with incident AS (1,111 patients) and controls (5,555 patients) matched by age, sex, income, and geographic region. The incidence rates of extra-articular manifestations (EAMs), comorbidities, mortality, and disability (type and severity) were compared between AS patients and controls. Annual health expenditure per patient was also analyzed. Associations were expressed as odds ratios (ORs) with 95% confidence intervals (95%CIs).During the follow-up, 28% of AS patients experienced at least one EAM. AS diagnosis was significantly associated with Charlson comorbidity index ≥3 (OR 2.18, 95% CI 1.91-2.48). Disability rate was higher in AS patients than in controls regardless of cause and severity (OR 2.94, 95% CI 2.48-3.48), but crude incidence rate ratios for mortality were not significantly higher. On multivariate analysis, male sex (OR 3.18, 95% CI 2.13-4.75), presence of an EAM (OR 1.63, 95% CI 1.15-2.32), and older age at diagnosis (OR 1.27, 95% CI 1.20-1.35) were evidently associated with increased disability in AS. Presence of an EAM was also associated with increased AS-unrelated expenditures in biologic-naïve patients (median, 1112 vs. 877 USD per person, P < 0.05).In patients with AS, demographic factors and systemic manifestations including EAMs and other comorbidities were associated with increased disability and healthcare expenditures.